Intermediate granulite produced by transformation of eclogite at a felsic granulite contact, in Blanský les, Bohemian Massif. (May 2014) - Štípská, P.; Powell, R.; Racek, M.; Lexa, O.
Abstract Layers or bodies of intermediate granulite on scales from a centimetre to a hundred metres occur commonly within the felsic granulite massifs of the Bohemian Massif. Their origin is enigmatic in that they commonly have complex microstructures that are difficult to interpret, and therefore even the sequence of crystallization of minerals is uncertain. At Kleť, in the Blanský les massif, there is a revealing outcrop in a low‐strain zone in which it is clear that intermediate granulite can form by the interaction of felsic granulite with eclogite. The eclogite, retains garnet from its eclogite heritage, the grains at least partially isolated from the matrix by a plagioclase corona. The original omphacite‐dominated matrix of the eclogite now consists of recrystallized diopsidic clinopyroxene, orthopyroxene and plagioclase, with minor brown amphibole and quartz. The modification of the eclogite is dominated by the addition of just K2O and H2O, rather than all the elements that would be involved if the process was one of pervasive melt infiltrations. This suggests that the main process involved is diffusion, with the source being the felsic granulite, or local partial melt of the granulite. The diffusion occurred at ~950 °C and 12 kbar, with the main observed effects being (i) the un‐isolation and preferential destruction of the interior part of some of the garnet grains by large idiomorphic ternary feldspar; (ii) textural modification of the matrix primarily involving the recrystallization of clinopyroxene into large poikiloblasts containing inclusions of ternary plagioclase; and (iii) conversion of low‐K plagioclase in the matrix into ternary feldspar by incorporation of the diffused‐in K2O. The phase equilibria in the intermediate granulite are consistent with the chemical potential relationships that would be superimposed on the original eclogite by the felsic granulite at 950 °C and 12 kbar.